HOW DO OPERATING LIQUIDITY AND FINANCIAL LEVERAGE INFLUENCE FIRM PERFORMANCE - Jamshaid, Fouzia; Kausar, Tayyiba; Ramirez-Asis, Edwin Hernan; Angulo-Cabanillas, Luis Elmer; Maldonado-Leyva, Hugo Walter (The journal of contemporary issues in business and government, 2021)
Operating liquidity and financial leverage are two important features of overall firm’s management. This study scrutinizes the association among financial leverage and different procedures of operating liquidity. Further the study has reconnoitered the joint effect of financial leverage and Operating liquidity on the performance of firm, for this purpose Return on Assets can be taken as the profitability that could gauge the profitability of firm and cement sector firms listed in Pakistan Stock Exchange have been taken as a population. For this purpose secondary data have been collected for 10 years from 2011 to 2020 through annual audited reports of sampled firms and through Business recorder. A casual research methodology has been used to explore results. Data was analyzed by using STATA software. For the sake of estimation, ratio Analysis and the panel dataregression model is incorporated to regress and construe association between the both dependent as well as the independent variables and want to find the cross sectional heterogeneity. Hausman test implies the presence of cross section heterogeneity hence, model move toward the fixed effect. Key results of the study imply that there is significant association among financial leverage and different measures of Operating liquidity. Furthermore from results of this study it is also concluded that financial leverage and Operating liquidity have noteworthy effect on cement sector performance of the firm. This study will help not only cement sector but also other sectors firms listed in Pakistan Stock Exchange by providing close eye view on relation between financial management and the operational management and their impact on firm Success or failure.